Plastic Mut(e)ability: Limited Promises of Plasticity - Tridibesh Dey (Ubiquity Press, 2021)
Plastics are supposed to be infinitely mutable. Yet the enduring legacies of plastic waste and its derivatives persist to tell a different tale. In this paper, based on empirical data from a rapidly urbanising village in Rajasthan, western India, we take the reader into the unfolding ‘social life’ of plastic (im)mutabilities. In tracing plastic’s complicity in configuring new objects, subject-object relations, markets, ensuing socio-economic hierarchies, and the ecological, biological and ethical traces of plastic waste, we present the picture of a plasticised socio-material realm. Here old socio-economic hegemonies and forms of violence are re-entrenched and new relations of deprivation and dependence forged in plastic, linked to wider (capitalist) processes of resource extraction, and abandonment. Therefore, we situate plastic’s multiple (im)mutabilities within an unfolding story of new openings, closures and mutations across scale, inflected by the complex legacies of caste, gender, race and region. Finally, the notion of plastic mut(e)abilities is developed to include occasions of productive hacks and crafts with plastic ‘waste’–ongoing plastic mutabilities–by a marginalised woman which allude to limited possibilities of socio-material change. This helps recover some of the promises of plastic co-produced at the delicate margins and the liminal spaces of a plasticised society.